Maria dalam Misteri Kristus dan dalam Hidup Gereja - Agus Widodo (P3TK, Sanata Dharma University, 2021)
Mary is a central figure in the Catholic Church. In fact, among the Christians, Mary who is a mere woman is more “popular” than Jesus who is God and savior. This can be seen in the Marian devotions and shrines which are far outnumber than the devotions and places of pilgrimage to Jesus. Mary is mother, not only for Jesus but also for the Church, that is, for all the faithful. This article will specifically discuss the life and role of Mary in the life of Jesus and the Church. Using the library research, this paper scrutinizes the Scriptures, the documents of the Church teachings, and some of liturgical texts which reveal the presence and the role of Mary in the life of Jesus and the Church. This article helps Christians to deep their knowledge and familiarity to Mary, and then to love her more and to emulate Her virtues in everyday life as believers.